Respuesta :

Answer:

[tex]{ \rm{2 { \sin }^{2} x - \cos x - 1 = 0 }} \\ \\ { \rm{2(1 - { \cos }^{2} x) - \cos x - 1 = 0}} \\ \\ { \rm{2 - 2 { \cos}^{2} x - \cos x - 1 = 0}} \\ \\ { \rm{2 { \cos }^{2}x + \cos x - 1 = 0 }} \\ [/tex]

• solving using quadratic formula:

[tex]{ \boxed{ \rm{x = \frac{ - b \pm \sqrt{ {b}^{2} - 4ac} }{2a} }}} \\ \\ { \rm{ \cos(x) = \frac{1 \pm \sqrt{9} }{8} }} \\ \\ { \rm{ \cos(x) = \frac{1}{2} \: \: or \: \: \frac{1}{4} }} \\ \\ { \boxed{ \tt{x = 60 \degree \: and \: \: 75.5 \degree}}}[/tex]

ACCESS MORE